Three days fast in sportsmen decreases physical work capacity but not strength or perception-reaction time - Gutierrez, A.; Gonzalez-Gross, M.; Delgado, M.; Castillo, M. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2001)
This study investigates, in young nonobese healthy athletes, the consequences of a 3-day fast coupled, or not, to enhanced physical activity. Eight male subjects, aged 21 ± 2 years, fasted for 3 days on two separate occasions, 4 weeks apart. On the first occasion, subjects continued their daily training activities. On the second occasion, a daily physical exercise program was added to these activities. Subjects were evaluated before and after 24 hours and 72 hours of fasting. Evaluation consisted of body composition, basal respiratory exchange ratio, plasma metabolic parameters, perception-reaction time (both simple and discriminant), hand grip strength, and physical work capacity at 170 beats per minute (PWC170). Fasting determined significant reductions in body weight, body fat, and muscle mass. These reductions were not affected by enhanced physical activity. Basal respiratory exchange ratio decreased with fasting but was not influenced by increased training activities. Fasting determined a significant decrease in blood glucose levels, while plasma proteins, urea, uric acid, and free fatty acids increased. Perception-reaction time and hand grip strength were unmodified during fasting. By contrast, PWC170 was significantly and progressively reduced during fasting, and this decrease was not reversed by an increase in training activities.